The Role of Men in the Economic and Social Development of Women : Implications for Gender Equality - Farré, Lídia (Oxford University Press on behalf of the World Bank, 2014)
This paper is a critical review of the literature on the issue of how male behavior affects female outcomes in the promotion of gender equality. It employs the family as the main unit of analysis because a large part of gender interactions occurs within this institution. This survey first summarizes recent studies on the distribution of power within the family and identifies several factors that have altered the bargaining position of men and women over the last decades. It then reviews empirical work on the contribution of men, as fathers and husbands, to the health and socioeconomic outcomes of women in both developed and developing countries. Finally, it discusses a set of economic policies that have intentionally or unintentionally affected men's attitudes and behaviors. The main implication is that policies meant to achieve gender equality should focus on men rather than exclusively target women.